Air quality in swine-finishing barns - B Z Predicala; Ronaldo G Maghirang; S B Jerez; J E Urban; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 2000)
Air quality was assessed in two commercial swine-finishing barns: one naturally ventilated (NV) and one mechanically ventilated (MV). The concentrations of inhalable dust (IDC), respirable dust (RDC), airborne viable particles, carbon dioxide (CO2), and ammonia (NH3), as well as the air temperature and relative humidity (RH) inside the barns were monitored for 41 weeks. The two barns did not differ significantly (P>0.05) in IDC, RDC, and bioaerosol concentration. Overall mean levels for IDC, RDC, CO2, and NH3 were below the threshold limit values specified by the American Conference of Governmental Industrial Hygienists (ACGIH). However, some measurements exceeded the exposure limits suggested by previous researchers, especially during cold days. In general, the air quality in the two types of buildings was acceptable except under certain conditions (e.g., low ventilation rates during cold weather). In such case, workers and producers may need help or further training to ensure adequate air quality. In addition, under these conditions, workers should wear respiratory protective devices to minimize risk of inhalation of dust, gases, and bioaerosols.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Indoor air quality; Livestock buildings; Airborne contaminants